ABNORMAL RETURN MOMENTUM PADA SAHAM SYARIAH DI JAKARTA ISLAMIC INDEKS - Nanda Nanda; Fajri Adrianto (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2019)
The purpose of this paper are to examine and analyse abnormal returns of momentum portofolio on Islamic stocks listed on the Jakarta Islamic Index 30 (JII 30) for the period 2010-2018. The method used in this study is Jagedeesh and Titmant (1993). Winner portfolio is formed by buying stocks with the best return performance in the past and selling stocks with bad returns in the past. Whereas a loser portfolio is formed by buying shares of poor return performance in the past and selling stocks with good returns in the past. Formations and observations used 1,3,6 and 12 months. With portfolio weighting based on equal-weighted and value-weighted. Abnormal return of momentum portofolio when winner minus loser positive. Significant contours are determined by a one-sample t-test using SPSS 25. The study did not find any abnormal return on the Islamic stocks listed on JII 30 for the period 2010-2018. But investors can still use this strategy to increase investment returns on Islamic stocks. Because this strategy still provides positive abnormal returns